PASAR BERKONSEP “TOUCH AND GO” DI TEPI SUNGAI CISADANE - Febriana Febriana; Agustinus Sutanto (Jurnal Sains, Teknologi, Urban, Perancangan, Arsitektur (Stupa), 2019)
Millennials determine Indonesia's face in the future. According to data from the National Development Planning Agency (Bappenas) there are 63 million millennials or people aged 20 - 35 years. They are in productive age. What needs to be considered is the need to encourage them to become the driving force of the Indonesian economy.The Old City of Tangerang is the name for a Chinatown which is the forerunner of the development of the City of Tangerang. But because of the intense development in this region and its surroundings, this region has lost its historical side. Tangerang City Government is trying to establish this area as a cultural tourism area. The existence of traditional markets in this region is not solely for economic affairs, but includes the contents of space and social relations, heritage and culture. The current condition of the Traditional Market Kisamaun is very concerning in terms of cleanliness and comfort, as well as facilities and infrastructure that are already very improper, and take areas that are not supposed to (in front of buildings that should be protected). Nevertheless, the interest of the surrounding community still does not diminish even though the market situation is not possible to visit. The price of cheap and competitive goods offered in the traditional market environment is the choice of some people. Because the existence of the Kisamaun Traditional Market is very important in the economic development of this city and historical region, it is necessary to do this Kisamaun Traditional Market Redesign. By not eliminating the parts that characterize this Chinatown, with the theme Vernacular Architecture of China. The vernacular approach of Chinatown is used in the design of this tourist market, with the aim of exploring the exoticism of cultural locality combined with contemporary contemporary tastes, so that this market can become a tourist destination. Abstrak Milenial menentukan wajah Indonesia ke depan. Menurut data Badan Perencanaan Pembangunan Nasional (Bappenas) ada 63 juta milenial atau penduduk usia 20 – 35 tahun. Mereka ada di usia produktif. Yang perlu diperhatikan adalah perlunya mendorong mereka agar menjadi roda penggerak ekonomi Indonesia. Kota Lama Tangerang adalah sebutan untuk sebuah kawasan pecinan yang merupakan cikal bakal berkembangnya Kota Tangerang. Namun karena gencarnya pembangunan di kawasan ini dan sekitarnya membuat kawasan ini kehilangan sisi historisnya. Pemkot Tangerang sedang berusaha menetapkan kawasan ini menjadi kawasan wisata budaya. Keberadaan pasar tradisional di kawasan ini bukan semata untuk urusan ekonomi, namun mencakup isi ruang dan relasi sosial, warisan dan budaya. Kondisi Pasar Tradisional Kisamaun saat ini sangat memprihatinkan dalam hal kebersihan dan kenyamanan, serta sarana dan prasarana yang sudah sangat tidak layak, dan mengambil kawasan yang tidak seharusnya (didepan bangunan yang seharusnya dilindungi). Walaupun demikian, minat masyarakat sekitar tetap tidak berkurang meskipun keadaan pasar sudah tidak memungkinkan untuk dikunjungi. Harga barang yang murah dan bersaing yang ditawarkan dalam lingkup pasar tradisional menjadi pilihan dari sebagian masyarakat. Oleh karena keberadaan Pasar Tradisional Kisamaun ini sangat penting dalam perkembangan perekonomian kota dan kawasan historis ini, maka perlu dilakukan Redesain Pasar Tradisional Kisamaun ini. Dengan tidak menghilangkan bagian – bagian yang menjadi ciri khas daerah pecinan ini, dengan tema Arsitektur Vernakular China. Pendekatan vernakular pecinan digunakan dalam desain pasar wisata ini, dengan tujuan menggali eksotisme lokalitas budaya yang digabung dengan selera kontemporer masa kini, sehingga pasar ini dapat menjadi destinasi wisata.